Peranan Koperasi Serba Usaha Mentibar Cemerlang Terhadap Kesejahteraan Anggota - Yopiana, Yopiana; Kusrini, Novira; Dolorosa, Eva (Jurnal Sosial Ekonomi Pertanian, 2024)
A Cooperative is a business entity that has a common social goal, namely to improve and improve the economy of people's lives which is based on the spirit of helping its members. This study aims to analyze the Role of the Mentibar Cemerlang Multi-Business Cooperative on the Welfare of Members in Mentibar Village, Paloh District, Sambas Regency. This research was conducted at the Mentibar Cemerlang Multi-Business Cooperative in Mentibar Village, Paloh District, Sambas Regency, the method of determining areas and objects was carried out purposively. The sample used in this study were 38 people who were members of KSU Mentibar Cemerlang and whose main job was as an oil palm farmer. This study used the SPSS analysis tool with the Rank-Spearman test. The results of this study show that there is a very strong relationship between the role of KSU Mentibar Cemerlang on the welfare of members with a correlation coefficient of 0.808 which is also positive, namely the type of relationship that is in the same direction, and a significant value of 0.000 is obtained.